Microbial response to deliquescence of nitrate-rich soils in the hyperarid Atacama Desert - F. L. Arens; A. Airo; A. Airo; C. Sager; C. Sager; H.-P. Grossart; H.-P. Grossart; K. Mangelsdorf; R. U. Meckenstock; M. Pannekens; P. Schmitt-Kopplin; P. Schmitt-Kopplin; et al. (Biogeosciences)
Life in hyperarid regions has adapted to extreme water scarcity through mechanisms like salt deliquescence. While halite (NaCl) crusts have been intensively studied and identified as one of the last habitats under hyperarid conditions, other less common hygroscopic salt crusts remain unexplored. Here, we investigated newly discovered deliquescent soil surfaces in the Atacama Desert, containing substantial amounts of nitrates, to evaluate their habitability for microorganisms. We characterized the environment with respect to water availability and biogeochemistry. Microbial abundances and composition were determined by cell cultivation experiments, 16S rRNA gene sequencing, and membrane phospholipid fatty acid (PLFA) analysis, while microbial activity was assessed by analyzing adenosine triphosphate (ATP) and the molecular composition of organic matter. Our findings reveal that, while the studied hygroscopic salts provide temporary water, microbial abundances and activity are lower in the studied soil surfaces than in non-deliquescent soil surfaces. Intriguingly, the deliquescent crusts are enriched in geochemically degraded organic matter, indicated by the molecular composition. We conclude that high nitrate concentrations in the hyperarid soils suppress microbial activity but preserve eolian-derived biomolecules. These insights are important for assessing the habitability and searching for life in hyperarid environments on Earth and beyond.